1987
DOI: 10.1107/s0108767387079558
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of triplet phases and enantiomorphs of non-centrosymmetric structures

Abstract: The X-ray standing wave technique for the localization of surface atoms has been used so far with crystals in the Bragg-case geometry. Since the standing wave intensity is modulated along the diffracting vector h, the Laue-case geometry with h nearly parallel to the surface is more preferable for the studies of lateral structures of the surface.For this purpose total exter~al reflection at grazing incidence angles is used to create a standing wave extending on both sides of the boundary surface (P. L. Cowan, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The special ~b-(six-)circle diffractometer described earlier (HiJmmer, Bondza & Weckert, 1987) was installed at the DORIS II storage ring at HASY-LAB/DESY, Hamburg. The angular resolution of the crystal circles was improved to 2 x 10 -4° The radiation was taken from a bending magnet at 3.65 GeV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The special ~b-(six-)circle diffractometer described earlier (HiJmmer, Bondza & Weckert, 1987) was installed at the DORIS II storage ring at HASY-LAB/DESY, Hamburg. The angular resolution of the crystal circles was improved to 2 x 10 -4° The radiation was taken from a bending magnet at 3.65 GeV.…”
Section: Methodsmentioning
confidence: 99%
“…The special ~b-(six-)circle diffractometer described earlier (HiJmmer, Bondza & Weckert, 1987) The fractional atomic coordinates were taken from: (1) Kartha & De Vries (1961); (2) Brown & Sadanaga (1965); (3) Hvoslef (1968) [warning: in this paper a left-handed coordinate system is used]; (4) Berman (1970); (5) Lehmann & Nunes (1980); (6) Burzlaff (1988); (7) Paulus (1988); (8) Weckert (1990a); (9) Weckert (1990b); (10) Weckert (1990c).…”
Section: Methodsmentioning
confidence: 99%
“…Primary reports indicate "chiral sensitivity with still too low confidence levee" [21]. As a promising but exclusive, due to unique instrumentation, alternative to the diffraction experiments described above, may be considered SR high resolution azimuthal scan [25].…”
Section: Discussionmentioning
confidence: 99%
“…Early works also included those by Hart and Lang on three-beam Pendellosung fringes [15] and by Ewald and Heno on theoretical aspects of three-beam dispersion surfaces [16]. The method was further developed in the 1980's by several groups [17][18][19][20] to show that the technique can be applied not only to perfect crystals but also to real, mosaic crystals. Furthermore, it was shown that the use of circularly polarized x-rays in a multiple-beam experiment can lead to additional phase information, especially for noncentrosymmetric systems [2 1,22].…”
Section: Introductionmentioning
confidence: 97%
“…The two diffracted waves interfere with each other and produce an asymmetric intensity profile in an azimuthal (psi) scan around one of the Bragg reflections. This intensity interference pattern depends directly on the relative phase of the two reflected waves, which can be shown equal to the triplet phase [15,[17][18][19][20] in crystallography. Therefore by measuring the three-beam interference patterns the triplet phases can be obtained directly in a diffraction experiment.…”
Section: Introductionmentioning
confidence: 99%